Early childhood nutrition, schooling, and sibling inequality in a dynamic context: evidence from South Africa - Yamauchi, Futoshi (International Food Policy Research Institute, 2006)
This paper examines the effects of early childhood nutrition on schooling inputs and outcomes to assess the dynamic nature of human capital production, using panel data from South Africa. Height-for-age Z-score is used as a measure of health and nutritional status in early childhood. Based on a comparison of siblings, this analysis concludes that improving children’s health significantly lowers the age when they start school, increases grade attainment, and decreases grade repetition in the early stage of schooling. However, this positive effect diminishes at later stages. The results also show that households allocate more of their resources (such as school fee expenditure) to healthy children at the early stage, although wealthier households may invest more in less well endowed children in an attempt to reduce sibling inequality. However, fewer resources are allocated to healthy children at later stages. By the time of transition from primary to secondary school, the healthy child can increase household income by seeking employment in the labor market. In other words, while health capital augments the efficiency of investment in schooling at the early stage, it may increase opportunity costs at the later stage, which may deter investment in schooling.